2015
DOI: 10.1556/crc.2014.0020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying inter-field movements of the western corn rootworm (Diabrotica virgifera virgiferaLeConte) — A Central European field study

Abstract: Dispersal plays a key role in the adaptation of species. It has been suggested that even in a stable and predictable environment, it is essential for any given population to "send" a certain portion of its offspring to disperse (referred as evolutionary stable dispersal rate). Although the literature on the flight behaviour of one of the major maize pests, the western corn rootworm, is rich, relatively little is known about its inter-field movements under field conditions. In the present study, inter-field mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…8 Principle 5-Protecting honeybees is one criterion used for pesticide selection and the profits it generates, introduction of a new crop nevertheless requires careful market considerations and additional inputs in terms of knowledge and machinery (Vasileiadis et al 2013). The rotation rule is therefore applied in a flexible way, adapting it to local conditions and allowing more frequent maize crops in a rotation and wider occurrence per farm area than theoretically optimal (Levay et al 2014;Szalai et al 2014). Rotating maize to a diversity of non-maize crop species helps farmers avoid the development of variant of the Western corn rootworm that is referred to as "rotation resistant" because of its propensity to oviposit in non-maize crops.…”
Section: Rotationmentioning
confidence: 99%
“…8 Principle 5-Protecting honeybees is one criterion used for pesticide selection and the profits it generates, introduction of a new crop nevertheless requires careful market considerations and additional inputs in terms of knowledge and machinery (Vasileiadis et al 2013). The rotation rule is therefore applied in a flexible way, adapting it to local conditions and allowing more frequent maize crops in a rotation and wider occurrence per farm area than theoretically optimal (Levay et al 2014;Szalai et al 2014). Rotating maize to a diversity of non-maize crop species helps farmers avoid the development of variant of the Western corn rootworm that is referred to as "rotation resistant" because of its propensity to oviposit in non-maize crops.…”
Section: Rotationmentioning
confidence: 99%
“…Research initiatives in the observed countries aimed to identify factors affecting adult and larval populations and damage at field level in Croatia [64,66,72,102,137,139], Hungary [78,162,231], Serbia [66,79,82,104,145,148,224], Slovenia, [53,76] and Romania [52,56,61,68,85,93,[97][98][99]140].…”
Section: Wcr Population Level Damage and Management Practicesmentioning
confidence: 99%
“…Different models may focus on different aspects of these two behaviors. Recent studies using mark-recapture techniques in response to the introduction of DVV into Europe have provided additional data that might be useful in modeling movement of DVV [ 46 , 47 , 48 ]. Estimates from all the above studies have suggested that between 24–38% of the adult DVV population engages in density-independent, long-distance dispersal.…”
Section: Fundamental Models Of Diabrotica Virgifera Virgmentioning
confidence: 99%
“…Estimates from all the above studies have suggested that between 24–38% of the adult DVV population engages in density-independent, long-distance dispersal. Higher densities may increase the proportion of beetles engaging in long distance dispersal [ 48 ], although Naranjo [ 49 ] found a negative relationship between larval density and sustained flight behavior in a flight mill study.…”
Section: Fundamental Models Of Diabrotica Virgifera Virgmentioning
confidence: 99%